A cross comparison of temporary work release programs as an alternative to incarceration within Canada and Ukraine - Shaw, Lauren (My University, 2022)
The goal of punishment through incarceration is to enforce ideals of criminal deterrence, provide retribution for victims of criminal activity, and to aid in the protection of society from offenders and criminal activity (Ward & Salmon, 2009). Methods of punishment by means of incarceration rely on the denial of access to opportunities and resources that are offered to members of society who are not criminals. By focusing on factors entailed in the idea of enforcing punishment via incarceration, the carceral system is not promoting offender reintegration into society, which increases likelihood of reoffending and thus perpetuates broken justice systems. There is an innumerable amount of evidence suggesting that punishment is not an effective method for the reduction of criminal activity. Therefore, due to a rise in prison populations, criminal activity and high recidivism rates, there is a need to review and modify the methods of the carceral system and offer reintegration programs for offenders (Cheliotis, 2008). This paper compares and contrasts the use of temporary work release programs within Canada and Ukraine and provides insight with regards to how the usage rates of temporary work release programs have changed over time since their implementation in legislation within Canada and Ukraine.
Keywords: incarceration; temporary work release programs